Quality of Hadith Luqath - Shilvi Rahma Adiningtias; Usep Dedi Rostandi (Gunung Djati Conference Series, 2021)
This study aims to discuss the quality of the traditions about luqathah and describe what is meant by luqathah. This research is a type of qualitative research that applies to both primary and secondary literature studies and uses the pentahrijan hadith method to determine the path of transmission and the quality of the hadith. The results and discussion of this study include an overview of luqathah, traditions about luqathah, and the quality of hadiths about luqathah. This study concludes that to determine the quality of hadith by mentakhrij hadith and i'tibar hadith to obtain information about the quality of hadith from the hadith literature, so that we can find out where the origin of the book of a hadith is, as well as the person who narrated it, so that it can clarify the condition of the chain. If the sanad and matan are combined, the overall quality of the hadiths about luqathah is authentic. This research recommends to do further on the quality of hadith about luqathah through field studies with an analytical approach to the study of sanad and matan hadith. This researcher is expected to have benefits for enriching the treasures of Islamic knowledge